2011
DOI: 10.1007/978-3-642-24500-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Experience: The Effects of Reading Game Reviews on Player Experience

Abstract: Abstract. Game reviews are used by game developers for making business decisions and measuring the success of a title, and have been shown to affect player perception of game quality. We conducted a study where players read positive or negative reviews of a game before playing, and show that the valence of review text affected game ratings and that these differences could not be explained by mediating changes in mood. Although we show predictable changes in player experience over the course of the study (measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Recently, only a few initial studies [31,57] analyzed this phenomenon by investigating differences and similarities in video game rating and review language of experts and amateurs, and we still lack a large-scale analysis of video game reviews. The facts that video game reviews impact (i) sales as estimated via numerous regression models [11,21,74,75], (ii) player experience as surveyed by multiple authors [28,42,43] and potentially even (iii) developer plans as implicated by the game piracy study of Drachen et al [17] further support our view that video game reviews pose a relevant and fertile testbed for comparing expert with crowdsourced inputs. Research Questions.…”
Section: Introductionsupporting
confidence: 58%
“…Recently, only a few initial studies [31,57] analyzed this phenomenon by investigating differences and similarities in video game rating and review language of experts and amateurs, and we still lack a large-scale analysis of video game reviews. The facts that video game reviews impact (i) sales as estimated via numerous regression models [11,21,74,75], (ii) player experience as surveyed by multiple authors [28,42,43] and potentially even (iii) developer plans as implicated by the game piracy study of Drachen et al [17] further support our view that video game reviews pose a relevant and fertile testbed for comparing expert with crowdsourced inputs. Research Questions.…”
Section: Introductionsupporting
confidence: 58%
“…The idea that players themselves have an effect on their game play is not novel, and some recent evidence suggests that players' interpretation of a game can change their experience significantly. Reading game reviews (Livingston et al, 2011) and referring to the ratings from external sources (Jenkins et al, 2010) affect the enjoyment of the game. Many players form an opinion about the game even before playing it, and this opinion may change their first encounter with the game.…”
Section: Immersion and Player Expectationsmentioning
confidence: 99%
“…An example a recent study by Livingston et al which found that negative content had more impact than positive content on a user's subsequent review of a game [36]. While positive priming can be used to positively influence perceptual accuracy, it is possible that the residual effects of positive emotions may negatively influence a higher-level task.…”
Section: Limitationsmentioning
confidence: 99%